Small Businesses in the Context of Innovation Competition - Biryukov, Vitaliy Vasilievich; Romanenko, Elena Vasilievna; Ploskonosova, Vera Petrovna; Bagno, Irina Gennadievna; Kalashnikova, Yuliya Vadimovna (International Journal of Economics and Financial Issues, 2015)
The article presents the results of the analysis and systematization of publications on the competitive behavior of small businesses in the innovation economy. It is shown that the adoption of innovation activity in small firms is an effective way of mass replication of innovations and is connected with the nonlinearity of the innovation process, the need for the accumulation and constant search for new knowledge and the successful adaptation to a changing business environment. In accordance with the presented in the article approach to the analysis of the competitive behavior of a small firm there were highlighted the motives (reasons) incorporating different forms of imitations in its innovation activity, individual objects of imitation, the range of factors affecting the success of the business. Suggestions put forward in this article are the basis of the author’s model of the impact made by innovative solutions on the performance of small businesses using imitations of varying degrees of creativity. Keywords: innovative economy; small business; imitation JEL Classifications: M13; M20; M21; M29